2017
DOI: 10.1155/2017/3824903
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cardiovascular Risks among Postmenopausal Women: A Community Based Case Control Study from Nepal

Abstract: Cardiovascular disease (CVD) is one of the leading causes of death worldwide which is more prevalent in women after menopause. Hormonal changes associated with menopause are accountable for dyslipidemic pattern that causes CVD and associated complications. Therefore, the present study was commenced to compare the lipid profile in pre- and postmenopausal women. A descriptive cross-sectional study was conducted at Manmohan Memorial Institute of Health Sciences (MMIHS) from February 2016 to July 2016. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 7 publications
7
42
1
1
Order By: Relevance
“…Although CVD is the major cause of death and disability in women, it usually starts about 10 years late in men of the same age. It is also true that CVD are the major cause of mortality in post-menopausal women 4 . The patterns of dyslipidemia that leads to CVD and its associated complications have been linked with hormonal changes associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CVD is the major cause of death and disability in women, it usually starts about 10 years late in men of the same age. It is also true that CVD are the major cause of mortality in post-menopausal women 4 . The patterns of dyslipidemia that leads to CVD and its associated complications have been linked with hormonal changes associated with menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVD) are the major cause of death among post-menopausal women 4 . Studies have shown that premenopausal women have a low risk of CVD as compared to men but after menopause the level of risk increases 5 .…”
Section: Introductionmentioning
confidence: 99%
“…CKD women experience kidney dysfunction-mediated premature menopause. In the postmenopausal period, women are more prone to develop diseases associated with estrogen deficiency, including heart diseases, osteoporosis, and dyslipidemia [88][89][90] due to hormonal changes involving the decrease in estrogen level and increase in luteinizing hormone (LH) and follicle stimulating hormone (FSH) levels. These changes exert significant effect on plasma lipid and lipoprotein metabolism [89,91].…”
Section: Postmenopausal Womenmentioning
confidence: 99%
“…Estrogen cardioprotective effect are related to the maintenance of high levels of HDL and low levels of LDL-C and triacylglycerols [90]. Estrogen regulates HDL levels directly by influencing mRNA production for specific protein, for example, proteins involved in lipid metabolism including lipoprotein lipase (LPL) and hormone sensitive lipase (HSL) in adipose tissue, and by promoting hepatic expression of apoprotein gene as well as indirectly through the impact on adipose tissue by stimulating release of other hormones, namely, growth hormone (GH), catecholamine, and glucagon, which increases activity of HSL [90,92]. 17-Beta-estradiol, which is a main circulating form of estrogen, increases the rate of apoA-I and apoA-II synthesis leading to higher HDL concentration [90].…”
Section: Postmenopausal Womenmentioning
confidence: 99%
See 1 more Smart Citation